CLE9 peptide‐induced stomatal closure is mediated by abscisic acid, hydrogen peroxide, and nitric oxide in Arabidopsis thaliana. (7th January 2019) - Zhang, Luosha; Shi, Xiong; Zhang, Yutao; Wang, Jiajing; Yang, Jingwei; Ishida, Takashi; Jiang, Wenqian; Han, Xiangyu; Kang, Jingke; Wang, Xuening; Pan, Lixia; Lv, Shuo; et al.
Abstract: CLE peptides have been implicated in various developmental processes of plants and mediate their responses to environmental stimuli. However, the biological relevance of most CLE genes remains to be functionally characterized. Here, we report that CLE9, which is expressed in stomata, acts as an essential regulator in the induction of stomatal closure. Exogenous application of CLE9 peptides or overexpression of CLE9 effectively led to stomatal closure and enhanced drought tolerance, whereas CLE9 loss‐of‐function mutants were sensitivity to drought stress. CLE9‐induced stomatal closure was impaired in abscisic acid (ABA)‐deficient mutants, indicating that ABA is required for CLE9‐medaited guard cell signalling. We further deciphered that two guard cell ABA‐signalling components, OST1 and SLAC1, were responsible for CLE9‐induced stomatal closure. MPK3 and MPK6 were activated by the CLE9 peptide, and CLE9 peptides failed to close stomata in mpk3 and mpk6 mutants. In addition, CLE9 peptides stimulated the induction of hydrogen peroxide (H2 O2 ) and nitric oxide (NO) synthesis associated with stomatal closure, which was abolished in the NADPH oxidase‐deficient mutants or nitric reductase mutants, respectively. Collectively, our results reveal a novel ABA‐dependent function of CLE9 in the regulation of stomatal apertures, thereby suggesting a potential role of CLE9 in the stress acclimatization of plants. Abstract : CLE peptides have been implicated in various developmental processes of plants and mediate their responses to environmental stimuli. Here, we reported an essential role of CLE9 in the induction of stomatal closure. CLE9 stimulated stomatal closure in an ABA‐dependent manner, accompanied with H2 O2 /NO production. Further investigation revealed that OST1, SLAC1, and MPK3/MPK6 are required for CLE9‐mediated guard cell signalling.